Mutual Regulation of Bcl-2 Proteins Independent of the BH3 Domain as Shown by the BH3-Lacking Protein Bcl-x(AK) - Plötz, Michael (Public Library of Science, 2012)

(untitled)
The BH3 domain of Bcl-2 proteins was regarded as indispensable for apoptosis induction and for mutual regulation of family members. We recently described Bcl-x(AK), a proapoptotic splice product of the bcl-x gene, which lacks BH3 but encloses BH2, BH4 and a transmembrane domain. It remained however unclear, how Bcl-x(AK) may trigger apoptosis. For efficient overexpression, Bcl-x(AK) was subcloned in an adenoviral vector under Tet-OFF control. The construct resulted in significant apoptosis induction in melanoma and nonmelanoma cell lines with up to 50% apoptotic cells as well as decreased cell proliferation and survival. Disruption of mitochondrial membrane potential, and cytochrome c release clearly indicated activation of the mitochondrial apoptosis pathways. Both Bax and Bak were activated as shown by clustering and conformation analysis. Mitochondrial translocation of Bcl-x(AK) appeared as an essential and initial step. Bcl-x(AK) was critically dependent on either Bax or Bak, and apoptosis was abrogated in Bax/Bak double knockout conditions as well by overexpression of Bcl-2 or Bcl-x(L). A direct interaction with Bcl-2, Bax, Bad, Noxa or Puma was however not seen by immunoprecipitation. Thus besides BH3-mediated interactions, there exists an additional way for mutual regulation of Bcl-2 proteins, which is independent of the BH3. This pathway appears to play a supplementary role also for other proapoptotic family members, and its unraveling may help to overcome therapy resistance in cancer.